Seasonal changes in technological and nutritional quality of Mytilus galloprovincialis from suspended culture in the Gulf of Trieste (North Adriatic Sea). (15th April 2015) - Bongiorno, Tiziana; Iacumin, Lucilla; Tubaro, Franco; Marcuzzo, Eva; Sensidoni, Alessandro; Tulli, Francesca
Highlights: Chemical composition and technological quality of Mytilus galloprovincialis is reported. High n-3/n-6 ratio values characterised the mussels reared in the Gulf of Trieste. Cr, Mn, Ni, Cu and Zn concentrations posed always no hazard to human health. A second order polynomial regression describes year around changes in condition index. Abstract: Nutritional quality parameters, microbiological and technological quality indicators (condition index, meat yield and water-holding capacity) of blue mussel, Mytilus galloprovincialis, reared in the North Adriatic Sea were characterised at monthly intervals over a 1 year period. Contents of protein (7.5–11.6 g/100 g), lipid (1.0–2.2 g/100 g) and ash (2.2–3.3 g/100 g) varied significantly accordingly to condition index (6–15%). n-3 PUFAs were the predominant fatty acids (38.7–45.9% of fatty acids) and docosahesaenoic and eicosapentaenoic acids were the most abundant (167 and 93.3 mg/100 g, respectively). Glycine, glutamic and aspartic acids accounted for 40% of total amino acids. All samples exhibited limited concentrations of Cr, Mn, Ni, Cu and Zn, as well as Na. M. galloprovincialis from the North Adriatic Sea showed the highest technological and nutritional quality, considering also the inter-annual variability, in late spring, which corresponds to the period immediately before gamete release.